Perancangan Web Profile Berita Sebagai Sumber Informasi Tentang Gapoktan Purwajaya Menggunakan Aplikasi Figma - Yuliana Maharani; Subhan Hartanto; Agusdi Syafrizal (JURNAL VOKASI TEKNIK, 2025)
GAPOKTAN (Gabungan Kelompok Tani) Purwajaya is an organization that plays an important role in the development of the agricultural sector in Indonesia. However, the dissemination of information about GAPOKTAN Purwajaya's activities and programs is still not optimal. This research aims to design an informative and attractive news profile web using Figma application and Design Sprint method. The Design Sprint method was chosen because of its ability to produce design solutions in a short time through five stages: Understand, Diverge, Converge, Prototype, and Test. with data collection through interviews, observation, and document analysis. The design process begins with analyzing the needs of GAPOKTAN Purwajaya, generating various design ideas, selecting the best idea, creating a web prototype, and testing the prototype. Evaluation was conducted using the User Experience Questionnaire (UEQ).